Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

Effects of wastewater flow direction on sulfur-based autotrophic denitrification processes: operational patterns, denitrification performance and response mechanisms - Daheng Ren; Heng Dong; Wenke He; Zhiqiang Zuo; Xiangli Zeng; Xuchen Ba; Yang Yu; Haoran Xu; Guijiao Zhang; Ran Zeng; Jiamin Xu; Na Zhang; et al. (Chemical Engineering Journal, 2026)

Regulation mechanism of N2O and CH4 emissions during the pig manure composting amended with Polygonum Multiflorum Thunb - Ya-jun Duan; Hong-sheng Wu; Jiang-yu Yang; Zheng-tong Zhou; Tao-ran Shi; Cheng Cheng; Zhen-wei Li; Chun-fa Wu; Ming-chun Di; Yu-dong He; Feng-yi Hu (World Journal of Microbiology and Biotechnology, 2026)

Galectin-3 in systemic lupus erythematosus: a meta-analysis - Yang Wu; Li-Na Jiang; Jing-Ru Wu; Yi-Ran Lu; Ting-ting Lu; Ji-Min Zhu; Jing Li; Shanshan Xu; Bai-Kun Li; Cheng-Gui Miao; Yan-Mei Mao (Immunologic Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Investigation on the High Food Availability Zone in riparian areas: From the perspective of fish food supply - Xiangdong Pan; Shuang Ren; Jingjie Feng; Ran Li; Yi Duan; Xiaolong Cheng (Ecohydrology & Hydrobiology, 2026)

Unveiling the regulation of biochar and ferrihydrite on organic carbon stabilization, CH4 emission and microbial community in paddy soil - Ran Zhang; Yujing Gu; Linrui Zhong; Yuantao Xu; Fanzhi Qin; Hong Qin; Qian Liu; Jiali Cheng; Jiahui Lei; Jingwen Yan; Yi Yin; Yue Lu (Journal of Environmental Sciences, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Emergence of a novel porcine reproductive and respiratory syndrome virus strain inducing biphasic temperature fluctuations in Tianjin, northern China - Jia Wang; Yi-Han Lu; Bo-Han; Hai-Tao Yang; Xin-lei Li; Wen Sun; Shi-Qin Zhang; Zhuo-Ran Miao; Xue-Jiao Cheng; Chun-Xue You; Ying-Feng Sun (Research in Veterinary Science, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Simultaneous activation of pyroptosis and cGAS-STING pathway with iridium(III) thiophene complexes for enhanced oral squamous cell carcinoma sono-immunotherapy - Jia-Wen Chen; Peng Wang; Jia-Ying Zhou; Yi-Fei Luo; Yi-Ling Li; Jia-Yin Wu; Ling-Ran Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Orientation-aware seismic landslide hazard assessment utilizing deep transfer learning under pulse-like ground motions - Yu-Heng Yang; Yin Cheng; Ran Yuan; Wei Mei; Jun-Bo Xia; Yi He (Soil Dynamics and Earthquake Engineering, 2026)

Coupled CFD-DEM modeling of fine particles and fibers migration and clogging mechanisms in bridging regions - Ran Lin; Yinjian Huang; Jinzhou Zhao; Lan Ren; Zhihao Yu; Zhiqiang Li; Jianfa Wu; Yi Song; Cheng Shen (Computers and Geotechnics, 2026)

Deep Shale Matrix Permeability Evolution During Well Shut-In Under True Triaxial Stress - Jinzhou Zhao; Yanshan Guo; Zhihao Yu; Lan Ren; Ran Lin; Jianfa Wu; Yi Song; Cheng Shen (Rock Mechanics and Rock Engineering, 2026)

Promoting nitrogen removal in low C/N wastewater treatment by S0 packed-bed process: Post polishing or via disproportionating sulfidogenesis enhancement - Cong Fang; Guijiao Zhang; Wenwei Liao; Ran Zeng; Na Zhang; Bin Gao; Jiamin Xu; Chengyan Liu; Aijie Wang; Hao-Yi Cheng (Chemical Engineering Journal, 2025)

Genome-Wide Identification and Expression Profiling of Oryza Sativa Sulfotransferase Genes Associated with Oxyfluorfen and Fluroxypyr-Meptyl Metabolism - Li Qing Zeng; Xiao Yu Zhong; Nian Hua Teng; Xu Zhen Shi; Yi Zhuo Wang; Xi Ran Cheng; Ying Yu Zeng; Zhao Jie Chen (Tropical Plant Biology, 2025)

Identification, Characterization, and Expression Profiling of Oryza Sativa Betaine Aldehyde Dehydrogenase Genes Exposed to Realistic Environmental Contamination of Oxyfluorfen - Yi Zhuo Wang; Jun Jin Lu; Xu Zhen Shi; Ya Nan Qu; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Yan Hui Wang; Zhao Jie Chen (Tropical Plant Biology, 2025)

Identification, characterization, and expression profiling of putrescine synthesis genes associated with bentazone metabolism in Oryza sativa - Li Qing Zeng; Nian Hua Teng; Ying Yu Zeng; Zhi Jiang He; Yi Zhuo Wang; Zhi Zhong Zhou; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetic Resources and Crop Evolution, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China - Yi-RAN Huang; Yu-Cheng Wang; Xiao-Xuan Meng; Yu-Tao Xiang (Science Bulletin, 2025)

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Study on the influence mechanism of endogenous protein components on the characteristics of distiller's grains starch - Min Huang; Li Li; Xinran Cheng; Ran Qiu; Yi Wang; Xianjiang Zhou; Xuyan Zong (Food Chemistry, 2025)

Causal Relationship Between Serum Zinc Levels and Diabetic Kidney Disease (DKD): A Plasma Proteomics Mediation Study - Chunbo Zhao; Tingting Pan; Wei Liu; Fanqian Cheng; Xiaoxuan Zhao; Shuxin Yu; Yi Yang; Ran Zhang; Weixia Sun (Biological Trace Element Research, 2025)

Data-driven differentiable model for dynamic prediction and control in wastewater treatment - Yun-Peng Song; Wen-Zhe Wang; Yu-Qi Wang; Wan-Xin Yin; Jia-Ji Chen; Hao-Ran Xu; Hao-Yi Cheng; Fang Ma; Han-Tao Wang; Ai-Jie Wang; Hong-Cheng Wang (Water Research, 2025)

Feedback inhibition derived from hydrogen sulfide in microbial sulfidogenic process via elemental sulfur disproportionation - Guijiao Zhang; Hao-Ran Xu; Wenwei Liao; Jia-Min Xu; Na Zhang; Daheng Ren; Xuchen Ba; Wenyan Mao; Wenke He; Cong Fang; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

In situ transglutaminase cross-linking mediated protein-stabilized high internal phase emulsion gels to emulate dorsal adipose tissue: The role of continuous phase networks - Liang Guo; Yu-hang Xue; Yi-ran Zhang; Wen-yan Chen; Yao-siyi Yuan; Shen-shen Tian; Yue-Cheng Meng; Jie Chen (Food Chemistry, 2025)

Phenol-driven ammonium recovery from coal chemical wastewater in a bioelectrochemical system (BES) - Ran Zeng; Li-Hui Yang; Si-Yuan Zhai; Cheng-Yan Liu; Na Lin; Qing-Hua Ou-Yang; Yan-Hua Xu; Ai-Jie Wang; Hao-Yi Cheng (Journal of Hazardous Materials, 2025)

An emulsion gel made by waxy maize starch hydrogel incorporated with tea polyphenols/exopolysaccharides: Structure and stability properties, antioxidant and delivery function - Cuicui Duan; Shunan Hu; Ran Wang; Cheng Wu; Yi Zhang; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Sonneralignan A, a new lignan from the fruit of mangrove Sonneratia apetala - Yue-Yao Li; Jia-Lang Xia; Meng Bai; Kai Liu; Jin-Hua Wei; Zu-Ran Lv; Yong-Hong Liu; Cheng-Hai Gao; Xiang-Xi Yi (Natural Product Research, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Bed-immersion-ratio variation as an efficient strategy to regulate denitrification efficiency directionally in elemental sulfur packed-bed reactors - Guijiao Zhang; Hao-Ran Xu; Wenwei Liao; Jia-Min Xu; Na Zhang; Daheng Ren; Xinjie Chen; Wenyan Mao; Xiangli Zeng; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Boosting bioelectricity generation in bioelectrochemical systems with nitrogen-doped three-dimensional graphene aerogel anode - Yi-Xuan Wang; Xiao-Li Liu; Wen-Qiang Li; Yi-Ran Wang; Ke-Wan Li; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Accumulated inflammation and fibrosis participate in atrazine induced ovary toxicity in mice - Yi-Fan Yang; Si-Yao Cheng; Ya-Long Wang; Zhao-Ping Yue; Yu-Xi Yu; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2024)

LiF-enriched interphase promotes Li+ desolvation and transportation enabling high-performance carbon anode under wide-range temperature - Wenbin Luo; Kuo Li; Tu Ran; Di Ma; Xingkun Chen; Haisong Wang; Yi Cheng; Xiaofei Yang (Chemical Engineering Journal, 2024)

Seawater corrosive engineering assisted in-situ room temperature synthesis of Ni/Co/Fe trimetallic composition to achieve polyester plastics upgrading and green hydrogen production - Zhao-Hui Zhang; Zhi-Ran Yu; Yi Zhang; Alexandre Barras; Ahmed Addad; Pascal Roussel; Long-Cheng Tang; Sabine Szunerits; Rabah Boukherroub (Chemical Engineering Journal, 2024)

Taming the anchor and conversion of polyselenides with a self-reinforcing host in lithium–selenium batteries - Hongyan Li; Wenda Dong; Yueqiang Cao; Tarek Barakat; Marvin Laboureur; Mao-Jin Ran; Zhi-Yi Hu; Hongxian Zhang; Cheng-Bin Jin; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

Tissue-specific responses and interactive characteristics of crop-microbe "One Health" system to soil chromium and ofloxacin pollution - Jia-Min Xu; Yaru Zhang; Kai Wang; Guodong Zhang; Ying Liu; Hao-Ran Xu; Hu-Yi Zi; Ai-Jie Wang; Yao Lv; Kun Xu; Hao-Yi Cheng (Process Safety and Environmental Protection, 2024)

Improved efficiency and stability using a novel elemental sulfur-based moving-bed denitrification process - Jia-Min Xu; Hu-Yi Zi; Hao-Ran Xu; Yi-Fan Zhang; Da-Heng Ren; Ran Zeng; Gui-Jiao Zhang; Aijie Wang; Hao-Yi Cheng (Water Research, 2024)

Genome constitution and evolution of Elymus atratus (Poaceae: Triticeae) inferred from cytogenetic and phylogenetic analysis - Lu Tan; Dan-Dan Wu; Chang-Bing Zhang; Yi-Ran Cheng; Li-Na Sha; Xing Fan; Hou-Yang Kang; Yi Wang; Hai-Qin Zhang; Marcial Escudero; Yong-Hong Zhou (Genes & Genomics, 2024)

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

Insights into the response of nitrogen metabolism to sulfamethoxazole contamination in constructed wetlands with varied substrates - Ya-Ru Zhang; Jia-Min Xu; Hao-Ran Xu; Guo-Dong Zhang; Xian-Bin Liu; Hao-Yi Cheng (Bioresource Technology, 2024)

Tricarboxylic acid cycle metabolites: new players in macrophage - Ying Yang; Bing-Bing Cui; Jian Li; Jiao-Jiao Shan; Jun Xu; Cheng-Yong Zhang; Xiao-Tong Wei; Ri-Ran Zhu; Jing-Yi Wang (Inflammation Research, 2024)

Effects of salinity on sulfur-dominated autotrophic denitrification microorganisms: Microbial community succession, key microorganisms and response mechanisms - Zhuo-Ran Li; Xue-Ning Zhang; Hong-Cheng Wang; Hao-Yi Cheng; Ai-Jie Wang; Yan-Qing Zhang; Chong-Wei Cui; Yi-Lu Sun (Chemical Engineering Journal, 2023)

Abnormal activation of the Wnt3a/β-catenin signaling pathway promotes the expression of T-box transcription factor 3(TBX3) and the epithelial-mesenchymal transition pathway to mediate the occurrence of adenomyosis - Mengqi Li; Ting Li; Tingting Jin; Yi Chen; Lan Cheng; Qiheng Liang; Simiao Yan; Tingting Li; Qingzhen Ran; Wanqun Chen (Molecular Biology Reports, 2023)

Enhanced retention of surface-adsorbed atomic hydrogen through sulfidation of nano zerovalent iron for water decontamination - Guan-Nan Zhou; Jia-Qi Chen; Wen-Qiang Li; Chuan-Shu He; Li Gong; Xiao-Cheng Liu; Yi-Ran Wang; Dahong Huang; Yang Mu (Chemical Engineering Journal, 2023)

Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Bei-Jing Cheng; Tian-Lin Li; Hui Li; Ke Meng; Xing-Chen Meng; Jia Wang; Chun Wang; Lin-Sheng Yang; Xin-Yi Zhu; Ran Liu (Science of The Total Environment, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Design and operation insights concerning a pilot-scale S0-driven autotrophic denitrification packed-bed process - Yi-Lu Sun; Zhuo-Ran Li; Xue-Ning Zhang; Heng Dong; Zhi-Min Qian; Shan Yi; Wei-Qin Zhuang; Hao-Yi Cheng; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Microbial electrochemical technologies assisted nitrogen recovery from different wastewater sources: Performance, life cycle assessment, and challenges - Siyuan Zhai; Dexin Zhang; Wenzong Liu; Bo Wang; Bin Liang; Chengyan Liu; Ran Zeng; Yanan Hou; Hao-Yi Cheng; Aijie Wang (Resources, Conservation and Recycling, 2023)

Three-dimensional macroporous structure and surface carbon-coating modification of stainless-steel anode boost bioelectrocatalytic performance - Cheng-Yan Liu; Hao-Yi Cheng; Si-Yuan Zhai; Ran Zeng; De-Xin Zhang; Ai-Jie Wang (Chemical Engineering Journal, 2023)

The extract from aerial part of Scutellaria baicalensis regulates gut microbiota in rabbit fish: Replacement of antibiotic fighting against pathogenic bacteria - Yi-Teng Xia; Edwin Hok-Chi Cheng; Huai-You Wang; Lynn Hoi-Lam Zhang; Sheng-Ying Lin; Tina Ting-Xia Dong; Ran Duan; Qi-Wei Qin; Wen-Xiong Wang; Karl Wah-Keung Tsim (Aquaculture, 2023)

Whole-genome sequencing and comparative genomic analysis of a pathogenic Enterocytozoon hepatopenaei strain isolated from Litopenaeus vannamei - Libao Wang; Hui Li; Wenjun Shi; Yi Qiao; Pan Wang; Zhijun Yu; Ran Zhao; Runhao Hu; Hui Shen; Jie Cheng; Ge Jiang; Xintong Huang; et al. (Aquaculture International, 2023)

Ectopic expression of MmCYP1A1, a mouse cytochrome P450 gene, positively regulates stress tolerance in apple calli and Arabidopsis - Xiao-Na Wang; Fei Yang; Jiu-Cheng Zhang; Yi-Ran Ren; Jian-Ping An; Da-Yong Chang; Xiao-Fei Wang; Chun-Xiang You (Plant Cell Reports, 2023)

Flowering characteristics and mating system of Fritillaria cirrhosa (Liliaceae), an endangered plant in China - Yanzhu Ma; Zhijia Cui; Chun Ya Cheng; Ran Li; Haixu Wu; Ling Jin; Yi Ma; Zhenheng Wang (Brazilian Journal of Botany, 2022)

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Functional connectivity patterns of the subgenual anterior cingulate cortex in first-episode refractory major depressive disorder - Bochao Cheng; Yajing Meng; Yan Zuo; Yi Guo; Xiuli Wang; Song Wang; Ran Zhang; Wei Deng; Yingkun Guo; Gang Ning (Brain Imaging and Behavior, 2021)

Toxicity assessment of electrochemical advanced oxidation process-treated groundwater from a gas station with petrochemical contamination - How-Ran Chao; Danielle E. Que; Alisha C. Aquino; Yan-You Gou; Lemmuel L. Tayo; Yi-Hsien Lin; Ming-Hsien Tsai; Fu-Lin Hsu; I-Cheng Lu; Sheng-Lun Lin; Natwat Srikhao; Cherng-Gueih Shy; et al. (Environmental Monitoring and Assessment, 2020)

Effects of Hyperbaric Oxygen Therapy on Acute Myocardial Infarction Following Carbon Monoxide Poisoning - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Chien-Chin Hsu; Hung-Jung Lin; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2020)

Experimental investigation on the mechanical characteristics of gas-bearing coal considering the impact of moisture - Ming-yi Chen; Yuan-ping Cheng; Jing-chun Wang; Hao-ran Li; Ning Wang (Arabian Journal of Geosciences, 2019)

Risk of Myocardial Infarction After Carbon Monoxide Poisoning: A Nationwide Population-Based Cohort Study - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Hung-Jung Lin; Chien-Chin Hsu; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2019)

Potential health risk assessment through ingestion and dermal contact arsenic-contaminated groundwater in Jianghan Plain, China - Ran Li; Yi-Ming Kuo; Wen-wen Liu; Cheng-Shin Jang; Enmin Zhao; Liquan Yao (Environmental Geochemistry and Health, 2018)

Effects of indole-3-butytric acid on lead and zinc accumulations in Pseudostellaria maximowicziana - Zhi Ran; Cheng Chen; Fabo Chen; Ming’an Liao; Lijin Lin; Xiulan Lv; Qunxian Deng; Xun Wang; Jin Wang; Yi Tang; Huaxiong Li (Environmental Monitoring and Assessment, 2018)

L1CAM drives oncogenicity in esophageal squamous cell carcinoma by stimulation of ezrin transcription - Jin-Cheng Guo; Yang-Min Xie; Li-Qiang Ran; Hui-Hui Cao; Chun Sun; Jian-Yi Wu; Zhi-Yong Wu; Lian-Di Liao; Wei-Jiang Zhao; Wang-Kai Fang; En-Min Li; Li-Yan Xu; et al. (Journal of Molecular Medicine, 2017)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Combined Effect of Ozonized Water Pretreatment and Ozonized Flake Ice on Maintaining Quality of Japanese Sea Bass ( Lateolabrax japonicus ) - Fei Lu; Shu-Lai Liu; Ran Liu; Yi-Cheng Ding; Yu-Ting Ding (Journal of Aquatic Food Product Technology, 2012)

Fast Cleanup System Combined with a Dioxin-responsive Element-driven Luciferase Bioassay for Analysis of Polychlorinated Dibenzo-p-dioxins/furans in Sediments and Soils - How-Ran Chao; Ya-Fen Wang; Ding-Yan Lin; Yi-Ting Cheng; Tsui-Chun Tsou (Bulletin of Environmental Contamination and Toxicology, 2011)

Role of DNA in Bacterial Aggregation - Hui-Hui Liu; Yi-Ran Yang; Xin-Cheng Shen; Zhi-Ling Zhang; Ping Shen; Zhi-Xiong Xie (Current Microbiology, 2008)